OIL CROP POMACE AS A POTENTIAL SOURCEOF PROTEIN AND DIETARY FIBER - SERGHEEVA, Elena; NETREBA, Natalia (Journal of Engineering Science (Chişinău))
The oil industry market is promising worldwide, including in the Republic of Moldova. The growth of vegetable oil production has led to the formation of a large amount of waste –oil crop pomace (meal), which is usually discarded or used in small quantities as animal feed and becomes a serious environmental problem. The aim of this work is to analyze and study different kinds of oil crop pomace,which can be used as a functional ingredient in product development due to its beneficial components, dietary fiber, and protein. This review presents the classification of meals, the methods of their production, chemical composition, protein, and dietary fiber extraction methods, also their characteristics are discussed. Harmless extraction methods are preferred as they reduce the number of reagents used, reduce waste, and increase the yield. The review presents physicochemical parameters of protein concentrates, isolates, and dietary fibers, which are actively used for valuable food additives production, used as low-calorie ingredients or texture stabilizers in the formulations of various food products.